Determinant of Employee Performance With Gender As Moderation Variable in A College - Gofar, Abdul; Haryono, Haryono; Yulianto, Arief (Educational Management, 2021)
The performance of employees at College in Indonesia continues to be improved in order to improve the quality of education services so that the academic achievement of students can increase. The performance of employees is one of the determinants of College performance. Based on the results of preliminary observations from researchers, it was found that there was a decrease in the performance of employees characterized by the increasing late hours of employees. A literature review conducted by researchers found that it is possible that employee performance is influenced by compensation, work environment and organizational culture. Researchers also guess that there are differences between men and women on the influence of the compensation environment, work environment and organizational culture on employee performance. The number of samples in this study was determined using the Slovin method, which obtained samples of 75 respondents from 276 employees and random sampling was used to determine the sample of this study. SmartPLS 2.0 M3 is used by researchers in conducting analysis tests and data analysis methods using PLS. Based on the statistical tests conducted, it was found that compensation, work environment and organizational culture had an effect on employee performance regardless of gender, whereas when researchers entered gender it was seen that gender succeeded in moderating the influence of compensation and work environment on employee performance but failed to moderate the influence of organizational culture on employee performance.